Microstructural and Mechanical Properties Study of Al/SiC composite prepared by PM technique - Al-Taa’y, Wasan A.; Mahmood, Mustafa A.; Al-Beayaty, Mohammed Ali H.; Abbas, Luma J. (Iraqi Journal of Science, 2025)
The present work investigates the optimal effect of SiC addition on the mechanical and microstructure properties of Al/SiC composites. The samples were prepared using powder metallurgy (PM) technique. Different weight percentages ranging from 10% to 50% of SiC powder were added and mixed with Al. The particle size of SiC particulates ranged between 20 and 45 μm. The subsequent mixture was poured into a cylindrical steel mould and pressed to obtain cylindrical shape samples of 10 mm in diameter. The prepared compact samples were sintered at a temperature of 650˚C. The influence of adding different weight percentages of SiC on the microstructure and mechanical characteristics of the composite was investigated. The XRD diffraction and SEM micrographs specified that Al and SiC were the main components in the composite. Ultimate strength was obtained for the addition of 20wt%SiC. Micro-hardness decreased due to porosity in proportionality to SiC content and the intermetallic phase formation. The present investigation showed that the optimum increase in microhardness was achieved between 20 to 40wt% of SiC, while the minimum hardness was at more than 40% SiC. On the other hand, the ultimate compressive strength was achieved between 10 to 30wt% of SiC and minimum compressibility was obtained at 50% SiC. Thus, the excessive addition of SiC leads to adverse results since it affects the composite porosity.